Validating the 2-minute walk test MCID for subacute stroke patients: A Pakistani multicenter cohort analysis - Muslim Khan; Hafiz Shehzad Muzamil; Ahmad M Osailan; Ayman Abdullah Alhammad; Samiullah Khan; Mazhar Mushtaq; Engy BadrEldin Saleh Moustafa; Theeb Naif S. Alsalem; Edward Muteesasira (PLoS ONE, 2026)
Background The 2-Minute Walk Test (2MWT) is a simple and reliable test used by clinicians to evaluate mobility gains in stroke populations. Objective To determine the minimally clinically important difference (MCID) for the 2-Minute Walk Test (2MWT) in subacute stroke populations. Design This was a prospective cohort study. Setting The study was carried out across seven rehabilitation centers in Pakistan. Participants 150 adults (<180 days post-stroke),with a confirmed ischemic or hemorrhagic stroke, able to walk at least 10 meters, and Mini-Mental State Examination score ≥24. Interventions Participants underwent 6–8 weeks of standard rehabilitation, including physical therapy (gait and balance training) and, in some centers, robotic gait training. Interventions varied by center but followed standardized gait and balance goals. Main outcome measures The 2MWT was the primary outcome measure whereas, the Activities-specific Balance Confidence gait subscale (ABC_Gait), Global Perceived Effect (GPE) scale, and Modified Barthel Index (MBI) were the secondary outcome measures. The MCID was estimated using an anchor-based approach (ABC_Gait ≥10% improvement), validated by distribution-based methods. Results The 2MWT MCID was 33 meters (95% CI: 30–36 meters), with 87% sensitivity and 82% specificity. A strong correlation was observed between 2MWT and ABC_Gait change scores (r = 0.68, p < 0.001). The mean 2MWT distance improved from 62.5 ± 38.4 meters to 98.7 ± 42.1 meters (p < 0.001). Subgroup analyses showed that MCID was consistent across age groups, stroke types, and intervention modalities. Conclusion The 33 meters MCID for the 2MWT is a reliable and patient-centered benchmark for assessing mobility gains in subacute stroke populations. Validation in chronic stroke populations and exploration of emerging interventions like virtual reality (VR) is needed to extend the 2MWT MCID’s applicability.